Effect of variation in the apo A-IV gene on body mass index and fasting and postprandial lipids in the European Atherosclerosis Research Study II - Rachel M. Fisher; Heidi Burke; Viviane Nicaud; Christian Ehnholm; Steve E. Humphries (Journal of Lipid Research, 1999)
The aims of the study were to investigate associations of the apolipoprotein (apo) A-IV polymorphisms Thr347Ser and Gln360His with anthropomorphic measurements and fasting and postprandial lipids in subjects participating in the European Atherosclerosis Research Study II (EARS II). The allelic frequencies of Ser347 and His360 were 0.185 and 0.067, respectively, in the sample as a whole. There were no significant differences in rare allele frequency between cases (offspring of fathers who suffered a myocardial infarction before the age of 55 years) and controls. Control subjects who were carriers of Ser347 had significantly higher body mass indices (BMIs), waist:hip ratios, total and low density lipoprotein cholesterol and triacylglycerol (TG) concentrations (all P ≤ 0.02) than control subjects who were non-carriers, but these effects were not seen in the cases. Control subjects who were carriers of His360 had lower BMIs (P = 0.04), cholesterol and TG concentrations (both P ≤ 0.07) compared to non-carriers, but these effects were not seen in the cases. After consumption of an oral fat load, carriers of His360 who were most obese (subjects in the third tertile of BMI) had significantly reduced postprandial lipemia (P < 0.03, as assessed by area under the curve).—Fisher, R. M., H. Burke, V. Nicaud, C. Ehnholm, and S. E. Humphries. Effect of variation in the apoA-IV gene on body mass index and fasting and postprandial lipids in the European Atherosclerosis Research Study II. J. Lipid Res. 1999. 40: 287–294.